Renal Dysfunction Is an Independent Risk Factor for Poor Outcome in Acute Ischemic Stroke Patients Treated with Intravenous Thrombolysis: A New Cutoff Value. (3rd January 2017) - Sadeghi-Hokmabadi, Elyar; Baş, Demet Funda; Farhoudi, Mehdi; Taheraghdam, Aliakbar; Savadi Oskouei, Daryoush; Yazdchi, Mohammad; Hashemilar, Maziyar; Uzuner, Nevzat; Mirnour, Reshad; Colak, Ertugrul; Özdemir, Atilla Özcan
Abstract : Objective . This study was set to assess the effect of renal dysfunction on outcome of stroke patients treated with intravenous thrombolysis (IVT). Methods . This multicenter research involved 403 patients from January 2009 to March 2015. Patients were divided into two groups: (1) control group with GFR ≥ 45 mL/min/1.73 m 2 and (2) low GFR group with GFR < 45 mL/min/1.73 m 2 . Outcome measurements were poor outcome (mRS 3–6) and mortality at 3 months and symptomatic intracerebral hemorrhage (SICH) within the first 24–36 hours. Univariate and multivariate regression analyses were performed, and odds ratios (ORs) were determined at 95% confidence intervals (CIs). Results . Univariate analyses determined that every decrease of GFR by 10 mL/min/1.73 m 2 significantly increased the risk of poor outcome (OR 1.19, 95% CI 1.09–1.30, p < 0.001 ) and mortality (OR 1.18, 95% CI 1.06–1.32, p = 0.002 ). In multivariate regression, adjusted for all variables withp value < 0.1, low GFR (GFR < 45 versus GFR equal to or more than 45) was associated with poor outcome (OR adjusted 2.15, 95% CI 1.01–4.56, p = 0.045 ). Conclusion . In IVT for acute stroke, renal dysfunction with GFR < 45 mL/min/1.73 m 2 before treatment determined increased odds for poor outcome compared to GFR of more than 45 mL/min/1.73 m 2 .